Greek crisis foreseen: the future in migrancy - Laliotou, Ioanna (The Greek Review of Social Research, 2013)
Ι discuss the impact of migration on the contemporary politics of culture in Greece. Ι use the term politics of culture in the broadest sense possible in order to include both official policies as well as everyday practices of meaning production. Ι focus on the ways in which migration is conceptualized and thematized around notions of community, gender, and future expectations. The article presents the findings of a collaborative research project that was conducted in the period 2004-2007. Discussion is based partly on original research and partly on theoretical elaborations of the interrelation between foreignness and nationalism. The findings of original research are revised in the light of the current context of political, economic and cultural crisis and political debates that the later has instigated. Analysis focuses on the study of the migrants’ emergent horizon of expectations and of the role that imaginary futures play in the formation of subjectivity.